“Don’t Forget about the Silver Covers!”: Newly Discovered Silverwork by the Armenian Silversmiths of Kayseri (Seventeenth–Eighteenth Centuries) - Merian, Sylvie L. (Matenadaran, 2024)
Abstract A seventeenth to eighteenth-century workshop of Armenian silversmiths from Kayseri, Cappadocia, is notable for having produced repoussé silver covers for religious manuscripts, liturgical objects, and luxury household articles. These objects were manufactured in silver, gold, or silvered copper, and were occasionally further embellished with colorful enamels and/or gems. Nearly seventy objects from this workshop have been identified; about a third are inscribed with the name of the silversmith and the date and place of production (Kayseri). Uninscribed objects created in this same workshop have been identified on the basis of technical and stylistic comparisons with the inscribed ones. This article will summarise the history of this workshop, discuss examples of the objects produced, and explain the iconography, which inspired the silversmiths. I will then introduce some newly identified objects from the workshop, a dish and bowl set in the collection of the Alex and Marie Manoogian Museum (Southfield, Michigan). The materials, technique of manufacture, and style confirm their origin in this Armenian atelier. The surprising inspirations for the motifs and iconography used in these pieces will also be explained. This article also includes the results of my provenance research as well as the fascinating findings of the Manoogian Museum’s scientific analysis of the objects. Possible future research will be proposed. It is hoped that by dissemination of further information about this workshop, more objects will be discovered, analyzed, and properly identified.
Keywords: silverwork